Enhancing the concentric tube properties by optimizing operational parameters. (2022) - Joe Patrick Gnanaraj, S.; Ramasamy, S.; Karthick, M.; George Klington, A.; Appadurai, M.
Abstract: Concentric tube warmth interchanger are used for multitude employment ranging from heat transfer for low cease packages to coolants in space cars. Typical heat alternate equations are sufficient to resolve problems related to finite temperature difference. However, scientific solutions require complicated calculations that considers losses and minute hast dissipations to offer accurate outcomes. Mathematical and analytical methods of counter go with the flow heat exchanger is carried out in this look at. Enumeration of heat change throughout counter float is facilitated by way of incorporating Runge-Kutta Method. Comparison among the two evaluation techniques is executed for 2 situations making use of NTU approach. During one of the conditions the input values had been maintained as same, all through the second one conditions, the input values were various. The Runge-Kutta Method gave correct results for both the situations.